ANALYSIS OF PHOTOCONVERSION CHARACTERISTICS AND PARAMETERS OF A HOLOGRAPHIC CONCENTRATOR FOR AN ENHANCED EFFICIENCY SOLAR CELL - Buktukov Nikolaj Sadvakasovic; Vasin Konstantin Andreevich (Academic Journal of Physical and Chemical Sciences, 2020)
The article describes the microprocessor method for measuring parameters and characteristics of conversion of solar radiation using a holographic concentrator at its production for an enhanced efficiency solar cell. The measurement is done using the Arduino Nano microprocessor controller, the HC-SR04 ultrasonic distance sensor, the TCS34725 color sensor, and the BH1750 light sensor. Information from the digital measuring system is transmitted via a serial USB port to a laptop where it is processed using the Excel spreadsheet. The developed system for determining the quality parameters and characteristics of the holographic concentrator ensures the obtainment of rational parameters for converting light flux and the necessary level of dispersion and focusing of solar radiation, which contributes to reaching the maximum efficiency of the solar cell.